2010
DOI: 10.2495/dne-v5-n2-142-159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of input waveforms in patient-specific right coronary atherosclerosis hemodynamics analysis

Abstract: Accurate fluid mechanics models are important tools for predicting the flow field in the coronary artery for understanding the relationship between hemodynamics and the initiation and progression of atherosclerosis. The purpose of this paper is to asses non-invasively hemodynamic parameters such as disturbed flows, pressure distribution and wall shear stress with computational fluid dynamics (CFD) in human right coronary artery (RCA) using patient-specific data from in vivo computed tomographic (CT) angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…An alternative means for invasive flow measurements is presented by the calculation of models in which blood flow can be virtually simulated, a method that is called computational fluid dynamics (CFD). In fact, several in vitro studies [6,10,16,17,18] have shown that CFD allows reliable physiologic blood flow simulation and measurements of WSS, wall pressure, and mass flow. A detailed hemodynamic evaluation of disturbed flow in the post stenotic region may give additional insight of the progression of atherosclerosis and may have useful clinical value, such as early detection of a highly stenosed artery segment, prediction of future disease progression, and treatment planning 2.1 Artery reconstruction A Somatom Sensation 64 Scanner (Siemens Medical Systems, Erlangen, Germany) was used in non-enhanced spiral scan technique with a slice thickness of 0.75 mm, a table feed of 1 mm/s, and an increment of 2 mm (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative means for invasive flow measurements is presented by the calculation of models in which blood flow can be virtually simulated, a method that is called computational fluid dynamics (CFD). In fact, several in vitro studies [6,10,16,17,18] have shown that CFD allows reliable physiologic blood flow simulation and measurements of WSS, wall pressure, and mass flow. A detailed hemodynamic evaluation of disturbed flow in the post stenotic region may give additional insight of the progression of atherosclerosis and may have useful clinical value, such as early detection of a highly stenosed artery segment, prediction of future disease progression, and treatment planning 2.1 Artery reconstruction A Somatom Sensation 64 Scanner (Siemens Medical Systems, Erlangen, Germany) was used in non-enhanced spiral scan technique with a slice thickness of 0.75 mm, a table feed of 1 mm/s, and an increment of 2 mm (Fig.…”
Section: Methodsmentioning
confidence: 99%